Effect of Combined Use of Astragaloside IV (AsIV) and Atorvastatin (AV) on Expression of PPAR-γ and Inflammation-Associated Cytokines in Atherosclerosis Rats - Sun, Bin (Med Sci Monit, 2018)
BACKGROUND: The aim of this study was to assess the effect of combined use of Astragaloside IV(AsIV) and atorvastatin (AV) on the expression of PPAR-γ and inflammation-associated cytokines in atherosclerosis rats. MATERIAL/METHODS: High-density lipoprotein cholesterol (HDL-C), total cholesterol (TC), and low-density lipoprotein cholesterol (LDL-C) in plasma were detected through automatic biochemical analyzer and the histopathological analysis was performed via HE staining. The levels of oxidized low-density lipoprotein (oxLDL) and tumor necrosis factor-α (TNF-α), and interleukins (IL)-6 and IL-18 in serum were detected by ELISA. The expressions of proliferator-activated receptor-gamma (PPAR-γ), cluster of differentiation 36 (CD36), matrix metalloprotein-9 (MMP-9), intercellular cell adhesion molecule-1 (ICAM-1) and vascular cell adhesion molecule-1(VCAM-1), and p38 and P-p38 levels were detected by Western blot. RT-PCR was used to detect the mRNA expressions of nuclear factor-κB (NF-κB), PPAR-γ, CD36, MMP-9, ICAM-1, and VCAM-1. RESULTS: Administration of AsIV and AV significantly decreased the lipid content and oxLDL in plasma. The levels of TNF-α, IL-6, and IL-18 were significantly decreased in AsIV, AV, and AsIV + AV groups, especially in the AsIV + AV group. Administration decreased the levels of NF-κB, CD36, MMP-9, ICAM-1, VCAM-1, and P-p38 expression and increased the expression of peroxisome PPAR-γ. Compared with the NC group, the atherosclerotic lesions significantly increased in the HD group, while the combined administration significantly inhibited the development of atherosclerotic disease. CONCLUSIONS: Combined administration of AV and AsIV showed potent effects against atherosclerosis through the NF-κB/PPARγ pathway, which may be a new therapy for treatment of atherosclerosis in the future.